(untitled) (Texas Journal of Medical Science, 2023)
The aim of the research is to identify the most important organizational concepts that contribute to improving the level of performance of physical education teachers in the General Directorate of Education in Salah al-Din, as well as to identify the reality of functional performance of physical education teachers in the General Directorate of Education in Salah al-Din, and the researcher assumed that there is a statistically significant relationship between the concepts. Organizational (organizational structure, procedures and work systems, communications, leadership styles, motivation, training) And the level of job performance of teachers of physical education in the General Directorate of Education in Salah al-Din, as well as the presence of statistically significant differences between the respondents’ answers about the relationship between organizational concepts and the level of job performance of teachers, which are attributed to the following variables (gender, age, educational qualification, degree, Years of experience, job type (administrative or technical), and the researcher relied on the descriptive approach because it expresses the social phenomenon to be studied quantitatively and qualitatively